Transformasi Digital dalam Sistem Informasi Perbankan Syari'ah: Masa Depan Keuangan yang Berkelanjutan - Emriana Parapat; Andrian Pebriansya; Irgi Prayogo; Nurbaiti Nurbaiti (Jurnal Sistem Informasi dan Ilmu Komputer, 2024)
This research is based on the devolment of Syapab banking in the digital era. The aim this research is to analyze the devilment of sharia banking in the digital era. This research investigates the development and introduction of Islamic banks in the digital era, which is expected to help people without having to go the bank. This research uses library research methods, wich use data sources collected from books information technology-based financing services will be very helpful in increasing public services,access to information has become faster and easier and can accesed anytime and anywhere.